Therapist competence, therapy quality, and therapist training - Fairburn, C; Cooper, Z (2011)
Large numbers of therapists worldwide wish to receive training in how to deliver psychological treatments. Current methods of training are poorly suited to this task as they are costly and require scarce expertise. New forms of training therefore need to be developed that are more cost-effective and scalable. Internet-based methods might fulfil these requirements whilst having the added advantage of being able to provide trainees with extensive exposure to the treatment as practised. New strategies and procedures for evaluating training outcome are also required. These need to be capable of assessing the therapist's knowledge of the treatment and its use, as well as the therapist's ability to apply this knowledge in clinical practice. Standardised role play-based techniques might be of value in this regard. © 2011 Elsevier Ltd.